The Factors Correlating to the Usage of Long-Term Contraception Method (MKJP) Especially IUD in the Domain of Society Health Center Simpang Baru Pekanbaru City - Wardani, S; Fitria, E (KnE Life Sciences, 2019)
Looking at the development of Long Term Contraception Method (henceforth; MKJP) usage during some periods, apparently the usage of IUD continues to decrease. The purpose of this research is to know the correlation between knowledge, couple agreement, culture, and the usage of MKJP especially IUD. The type of this research was quantitative research, with cross sectional design. The total population of MKJP users were 621 people. The samples taken were 243, the technique of taking the samples were through systematic random sampling. The result of chi-square test obtained that there is correlation between knowledge and the usage of MKJP especially IUD with the score of p-value = 0,00. There is correlation between the spouse support and the usage of MKJP especially IUD with the score of p-value = 0,013. The score of OR 5,15. There is correlation between the culture and the usage of MKJP especially IUD with the score of p-value = 0,019, the score of OR 5,41. The most dominant variable correlating to the usage of MKJP especially IUD is the spouse support. It means respondents who have negative support from their spouses have chance to not using MKJP especially IUD. It is expected to the policy maker to create programs as an effort to improve the knowledge of the society through socialization, leaflet, and other media, activating the agent in the field, synergy across sector, public figure, until giving understanding, mindset, trust, capability, and spouse support which results in creating the culture of using MKJP especially IUD. Keywords: MKJP, IUD, knowledge, spouse support, culture